Invoicing of storage costs for ready-to-deliver goods in case of delayed pick-up from the customer : Encouraging collection of finished goods - Jokinen, Niko (My University, 2024)
The research investigates the integration of invoicing for storage costs of ready-to-deliver goods when customer pick-up is delayed, focusing on its impact on operational business processes. The theoretical framework is based on contract management theories and supply chain practices while exploring how contracts and invoicing can improve operational efficiency and customer relationships. This integration is seen as a factor in reducing the risks associated with delayed delivery of products. The objective of the study is to examine the critical factors for successfully integrating storage cost invoicing into business processes and to assess its organizational implications and provide recommendations for middle management. These research questions are intended to increase understanding of the logistical and financial implications of introducing such invoicing methods and to provide the case study company with practical insights to improve its current operations and cost management. The study uses a simple mixed methods approach, using both qualitative and quantitative methods to investigate the key factors to consider when integrating contract and storage cost invoicing into business operations and the implications of integrating the two for the business process. The qualitative method is implemented in the form of a comprehensive literature review, which provides the framework for the study based on numerous prior and peer-reviewed academic references. The quantitative method studies more the implications for the organization based on order and product data collected over a five-year period from a case company's ERP system. The compiled database consists just under a hundred thousand units, which constitutes a representative sample of the population, and is used statistically to analyse the potential impact that this work can contribute to improving operational performance. The results show that the key factors for contract integration are clear contract guidelines, legality, definition of responsibilities and communication, while the key factors for storage cost invoicing are operational and financial monitoring, resource planning and alignment of responsibilities and consequences. In addition, the implications for business processes show that more than a fifth of the sample is delayed due to customer pick-ups, which is equivalent to almost a quarter of the value of manufacturing production highlighting the importance of this study while providing additional revenue streams. To address these practical concerns, the study proposes strategies to improve business efficiency and customer responsibility through appropriate invoicing mechanisms. These results contribute to both the academic literature and practical applications by providing a model for improving inventory management, reducing additional costs due to delays, and aligning business processes with contractual responsibilities. The research provides a framework for further improvements in inventory cost management, in particular how organizations balance operational efficiency and customer service.

Tutkimuksessa tutkitaan toimitusvalmiiden tavaroiden varastointikustannusten laskutuksen integrointia, kun asiakkaan nouto viivästyy, ja keskitytään sen vaikutukseen liiketoimintaprosesseihin. Teoreettinen viitekehys perustuu sopimusten hallinnan teorioihin ja toimitusketjun käytäntöihin, ja samalla tutkitaan, miten sopimukset ja laskutus voivat parantaa toiminnan tehokkuutta ja asiakassuhteita. Tätä integrointia pidetään tekijänä, joka vähentää tuotteiden viivästyneeseen toimitukseen liittyviä riskejä. Tutkimuksen tavoitteena on tarkastella kriittisiä tekijöitä, jotka liittyvät varastointikustannusten laskutuksen onnistuneeseen integrointiin liiketoimintaprosesseihin, ja arvioida sen organisatorisia vaikutuksia ja antaa suosituksia keskijohdolle. Näiden tutkimuskysymysten tarkoituksena on lisätä ymmärrystä tällaisten laskutusmenetelmien käyttöönoton logistisista ja taloudellisista vaikutuksista ja antaa case-yritykselle käytännön näkemyksiä sen nykyisten toimintojen ja kustannustenhallinnan parantamiseksi. Tutkimuksessa käytetään yksinkertaista sekamenetelmää, jossa käytetään sekä kvalitatiivisia että kvantitatiivisia menetelmiä tutkimaan keskeisiä tekijöitä, jotka on otettava huomioon in-tegroitaessa sopimus- ja varastointikustannusten laskutusta liiketoimintaan, sekä näiden kah-den yhdistämisen vaikutuksia liiketoimintaprosessiin. Kvalitatiivinen menetelmä toteutetaan kirjallisuuskatsauksen muodossa, joka muodostaa tutkimuksen kehyksen lukuisille ajankohtais¬ten ja vertaisarvioitujen akateemisten lähteiden avulla. Kvantitatiivisella menetelmällä tutkitaan enemmän organisaatioon kohdistuvia vaikutuksia, jotka perustuvat case-yrityksen ERP-järjestel¬mästä viiden vuoden ajalta kerättyihin tilaus- ja tuotetietoihin. Kootussa tietokannassa on muu¬tama vähän alle satatuhatta yksikköä, mikä muodostaa edustavan otoksen perusjoukosta, ja sitä käytetään tilastollisesti analysoimaan mahdollisia vaikutuksia, joita tämä työ voi edistää opera¬tiivisen suorituskyvyn parantamisessa. Tulokset osoittavat, että sopimusten integroinnin avain¬tekijöitä ovat selkeät sopimusohjeet, laillisuus, vastuiden määrittely ja kommunikointi, kun taas varastointikustannusten laskutuksen avaintekijöitä ovat toiminnallinen ja taloudellinen seu¬ranta, resurssien suunnittelu sekä vastuiden ja seurausten yhdenmukaistaminen. Lisäksi vaiku¬tukset liiketoimintaprosesseihin osoittavat, että yli viidennes otoksesta viivästyy asiakkaiden noutojen vuoksi, mikä vastaa lähes neljäsosaa valmistustuotannon arvosta. Näiden käytännön ongelmien ratkaisemiseksi tutkimuksessa ehdotetaan strategioita liiketoiminnan tehokkuuden ja asiakkaiden vastuuvelvollisuuden parantamiseksi asianmukaisten laskutusmekanismien avulla. Tulokset edistävät sekä akateemista kirjallisuutta että käytännön sovelluksia tarjoamalla mallin, jolla voidaan parantaa varastonhallintaa, vähentää viivästyksistä aiheutuvia lisäkustannuksia ja sovittaa liiketoimintaprosessit yhteen sopimusvelvoitteiden kanssa. Tutkimus tarjoaa puitteet varastokustannusten hallinnan parantamiselle edelleen, erityisesti sille, miten organisaatiot tasapainottavat toiminnan tehokkuutta ja asiakaspalvelua.
Keywords: contract management; supply chains; costs; logistics; invoicing; fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management